2008
DOI: 10.1037/1082-989x.13.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Constrained versus unconstrained estimation in structural equation modeling.

Abstract: Recently, R. D. Stoel, F. G. Garre, C. Dolan, and G. van den Wittenboer (2006) reviewed approaches for obtaining reference mixture distributions for difference tests when a parameter is on the boundary. The authors of the present study argue that this methodology is incomplete without a discussion of when the mixtures are needed and show that they only become relevant when constrained difference tests are conducted. Because constrained difference tests can hide important model misspecification, a reliable way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 50 publications
2
81
0
Order By: Relevance
“…We then controlled these two coefficients to be equal and re-ran the estimation in the constrained structural model. The results indicated that the constrained model fitted to the data worse than the unconstrained model [Dv 2 (1) = 3.851, p \ .05], suggesting that the regression weight between green management and radical product innovation was significantly stronger than that between green management and incremental product innovation (Savalei and Kolenikov 2008). Thus, H1 was supported.…”
Section: Resultsmentioning
confidence: 47%
“…We then controlled these two coefficients to be equal and re-ran the estimation in the constrained structural model. The results indicated that the constrained model fitted to the data worse than the unconstrained model [Dv 2 (1) = 3.851, p \ .05], suggesting that the regression weight between green management and radical product innovation was significantly stronger than that between green management and incremental product innovation (Savalei and Kolenikov 2008). Thus, H1 was supported.…”
Section: Resultsmentioning
confidence: 47%
“…Standard Z-tests may be appropriate in such situations, since the parameter space is no longer bounded and the null value is no longer on the boundary of the parameter space. Interested readers are referred to Savalei and Kolenikov (2008) for a more thorough discussion of constrained versus non-constrained variance component estimates.…”
Section: Level-2 Variance Component Point Estimate Simulation Study Fmentioning
confidence: 99%
“…For sample size 200 and 2 response categories, despite the convergence rate being 100% for all three methods, the rate of proper solutions is 97.8% for PML and DWLS and 94.9% for ULS. The results regarding the test statistics reported below are based on the total number of replications because the full output is produced for all of them and improper solutions are expected to happen in small sample sizes and do not necessarily represent a statistical anomaly (Savalei & Kolenikov, 2008;Savalei & Rhemtulla, 2013). Figure 1 gives the empirical type I error rates for each method and experimental condition.…”
Section: On the Performance Of Plrt For Overall Fitmentioning
confidence: 99%